The Experience of the Internal Auditor in Reducing the Penetration of Computerized Data and its Effect on the Bank Continuity: Evidence from the Emerging Markets - Abdulazeez Sahib, Shaimaa; Wahhab, Asaad Mohammed Ali (Technium Social Sciences Journal, 2023)
This study aims to identify the challenges facing internal auditors in light of information technology, as well as measure the effect of the auditor’s experience under information technology on reducing the penetration of computerized accounting data and provide practical solutions for internal auditors in Iraqi banks to develop their professional skills in light of information technology. To accomplish these objectives, a data collection instrument consisting of 211 questionnaires was designed and distributed to internal auditors at Iraqi banks listed on the Iraq Stock Exchange. Appropriate statistics in testing hypotheses led to the conclusion that banks are exposed to risks through data penetration in the presence of information technology, which affects their long-term success due to the internal auditor’s lack of adequate experience in the field of computer and information technology.